Letters from your editor: Should tropical researchers enter the racist “Millionaire’s Club”? - Monge-Nájera, Julián (2018)
Letters from your editorSometimes, the editors of the large journals published in rich countries discriminate against the authors of tropical countries because of prejudice and not because of manuscript quality. Tropical researchers have two options: insist on publishing in these journals of the so called “Millionaire’s Club”, where there is often a natural disinterest in tropical issues; or to support the development of good tropical quality journals. The second option has ethical and practical advantages for everyone.